Understanding humoral immunity and multiple sclerosis severity in Black, and Latinx patients - Telesford, Kiel M.; Amezcua, Lilyana; Tardo, Lauren; Horton, Lindsay; Lund, Brett T.; Reder, Anthony T.; Vartanian, Timothy; Monson, Nancy L. (Frontiers in Immunology, 2023)
People identified with Black/African American, or Hispanic/Latinx ethnicity are more likely to exhibit a more severe multiple sclerosis disease course relative to those who identify as White. While social determinants of health account for some of this discordant severity, investigation into contributing immunobiology remains sparse. The limited immunologic data stands in stark contrast to the volume of clinical studies describing ethnicity-associated discordant presentation, and to advancement made in our understanding of MS immunopathogenesis over the past several decades. In this perspective, we posit that humoral immune responses offer a promising avenue to better understand underpinnings of discordant MS severity among Black/African American, and Hispanic/Latinx-identifying patients.